The Use of Audio-Visual Media in Improving the Ability to Listen to Fairy Tales of Elementary School Students - Syane Ina Darisera; Ribka L Ririhena; Zainudin Notanubun (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This research is motivated by the low ability to listen to fairy tales in fourth-grade students at Elementary School 2 Ambon, which is indicated by the students' failure to achieve the Minimum Completion Criteria in the Indonesian Language subject. The main objective of this research is to improve students' ability to listen to fairy tales through the implementation of audio-visual media. We conduct Classroom Action Research (CAR) in two cycles. The research subjects consisted of 20 fourth-grade students at Elementary School 2 Ambon. The research procedures in each cycle include the stages of planning, implementation, observation, and reflection. The study's findings demonstrate that the utilization of audio-visual media significantly enhances students' listening skills by facilitating the visualization of tangible characters and narrative settings. The effectiveness is evidenced by a significant increase in the classical average score, from the pre-cycle condition of 48.9% (very poor category) increasing to 58.1% in cycle I and reaching 78% in cycle II, which is included in the good category. At the end of cycle II, all students (100%) successfully achieved the minimum completion criteria of ≥ 70 with improvements in the aspects of content understanding (29%), identification of intrinsic elements (23.95%), and moral messages (25.05%). This study provides a practical contribution for teachers in innovating the use of technology-based learning media to optimize students' language competence at the elementary school level.